2020
DOI: 10.1002/cti2.1228
|View full text |Cite
|
Sign up to set email alerts
|

Trained immunity as a novel approach against COVID‐19 with a focus on Bacillus Calmette–Guérin vaccine: mechanisms, challenges and perspectives

Abstract: COVID‐19 is a severe health problem in many countries and has altered day‐to‐day life in the whole world. This infection is caused by the SARS‐CoV‐2 virus, and depending on age, sex and health status of the patient, it can present with variety of clinical symptoms such as mild infection, a very severe form or even asymptomatic course of the disease. Similarly to other viruses, innate immune response plays a vital role in protection against COVID‐19. However, dysregulation of innate immunity could have a signif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
33
0
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(36 citation statements)
references
References 123 publications
(266 reference statements)
2
33
0
1
Order By: Relevance
“…Pre-existing underlying health conditions such as diabetes, atherosclerosis, hypertension, cancer, immunocompromised states, chronic kidney disease, and overweight/obesity substantially increase COVID-19 mortality and morbidity. 1 In addition, COVID-19 severity drastically increases with advancing age. 2,3 In patients with severe disease, COVID-19 induces a complex dysregulation of both innate and adaptive immune responses, that sometimes result in a combination of inappropriate systemic inflammation (leading to pulmonary edema and respiratory insufficiency), as well as defects in specific components of the immune responses (e.g., interferon [IFN] pathway defects, lymphopenia), contributing to disease severity.…”
Section: Discussionmentioning
confidence: 99%
“…Pre-existing underlying health conditions such as diabetes, atherosclerosis, hypertension, cancer, immunocompromised states, chronic kidney disease, and overweight/obesity substantially increase COVID-19 mortality and morbidity. 1 In addition, COVID-19 severity drastically increases with advancing age. 2,3 In patients with severe disease, COVID-19 induces a complex dysregulation of both innate and adaptive immune responses, that sometimes result in a combination of inappropriate systemic inflammation (leading to pulmonary edema and respiratory insufficiency), as well as defects in specific components of the immune responses (e.g., interferon [IFN] pathway defects, lymphopenia), contributing to disease severity.…”
Section: Discussionmentioning
confidence: 99%
“…Although several reports have claimed that BCG is not effective in fighting COVID-19 [ 56–59 ], a growing number of studies have shown that countries with routine BCG vaccination programs have significantly fewer reported cases and deaths caused by COVID-19 [ 27 , 28 , 30 , 60–62 ]. However, these observational studies need to be further confirmed by clinical trials.…”
Section: Current Clinical Trials Of Tb Vaccines Against Covid-19mentioning
confidence: 99%
“…Currently, there is no direct evidence to support the use of the BCG vaccine for the prevention of coronavirus infections [ 31 ]. However, the available data show that the BCG vaccine provides nonspecific protection against lethal infections that are not related to the vaccine’s target pathogen by inducing trained nonspecific innate immune cells to improve host responses against subsequent infections [ 28 , 32 , 33 ]. Although induction of trained immunity (TI) by BCG vaccination leads to beneficial heterologous effects, the mechanisms underlying its persistence and magnitude remain unknown.…”
Section: Introductionmentioning
confidence: 99%
“…Several countries are conducting randomized clinical trials in vulnerable populations to study the possibility of increasing protection against COVID-19 through BCG vaccination. In addition, it is important to determine which BCG strain and which vaccine can produce the strongest immunity [193,194].…”
Section: Reviewsmentioning
confidence: 99%